2011
DOI: 10.1163/138855410x532168
|View full text |Cite
|
Sign up to set email alerts
|

Bursaphelenchus trypophloei sp. n. (Nematoda: Parasitaphelenchinae) – an associate of the bark beetle, Trypophloeus asperatus (Gyll.) (Coleoptera: Curculionidae, Scolytinae), in aspen, Populus tremula L.

Abstract: Bursaphelenchus trypophloei sp. n. is described from weakened and dead twigs of living or recently fallen aspen trees, Populus tremula, in Poland. All propagative stages of the nematode were present in larval galleries of a bark beetle, Trypophloeus asperatus, and its dauer juveniles could be found in the haemocoel of older larvae, pupae and adult beetles. Characteristic morphology of the male spicules with distinct cucullus, extended anterior vulval lip, lateral fields with four incisures, and number and arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It is probable that the difference in fungal composition introduced to the bark by each ash beetle species could be responsible for making this association so specific. Our earlier studies have revealed that B. trypophloei and B. masseyi developed specifically on fungi introduced to the bark of poplar by bark beetles which also served as exclusive vectors of these nematodes (Tomalak & Filipiak, 2011;Tomalak et al, 2013). However, further research is needed to elucidate the basis of the observed specificity.…”
Section: Discussionmentioning
confidence: 98%
“…It is probable that the difference in fungal composition introduced to the bark by each ash beetle species could be responsible for making this association so specific. Our earlier studies have revealed that B. trypophloei and B. masseyi developed specifically on fungi introduced to the bark of poplar by bark beetles which also served as exclusive vectors of these nematodes (Tomalak & Filipiak, 2011;Tomalak et al, 2013). However, further research is needed to elucidate the basis of the observed specificity.…”
Section: Discussionmentioning
confidence: 98%
“…The tree contained a highly supported major clade (PP = 1.0) comprising all the species of the genus Boleodorus, including the B. thylactus and B. volutus from Alberta, Canada (Figure 5). The D2-D3 domains of the 28S rRNA gene alignment (699 bp long) included 98 sequences of Tylenchidae species (four of them new, belonging to B. thylactus, and three others from B. volutus) and three outgroup species, Bursaphelenchus trypophloei Tomalak [73] (FJ998283), Bursaphelenchus mucronatus Mamiya and Enda [74] (AB932857), and Aphelenchoides fragariae (MK077677). The Bayesian 50% majority rule consensus tree inferred from the D2-D3 alignment shows one highly supported major clade (PP = 1.0) comprising species of Boleodorus, including B. thylactus and B. volutus from Alberta, Canada (Figure 6).…”
Section: Molecular Characterization Of B Thylactus and B Volutus With...mentioning
confidence: 99%
“…Bursaphelenchus species have been examined mostly for conifers. However, so far, many species have been also found from broadleaved trees in numerous places in the Northern Hemisphere (Braasch & Burgermeister, 2007; Kanzaki & Giblin‐Davis, 2018; Kurashvili et al., 1980; Ryss et al., 2015; Ryss & Subbotin, 2017; Tomalak & Filipiak, 2010, 2011; Tomalak et al., 2013). Further studies are necessary to determine the distribution of B. mucronatus and other Bursaphelenchus species on broadleaf forests and possible insect vectors in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to coniferous trees, some broadleaved tree species are also known to be the hosts of Bursaphelenchus species (Braasch & Burgermeister, 2007; Kanzaki & Giblin‐Davis, 2018; Ryss et al., 2005, 2015; Ryss & Subbotin, 2017; Tomalak & Filipiak, 2010, 2011; Tomalak et al., 2013). The presence of Bursaphelenchus species in broadleaved forest trees is not known in Turkey.…”
Section: Introductionmentioning
confidence: 99%